2015
DOI: 10.1097/scs.0000000000001852
|View full text |Cite
|
Sign up to set email alerts
|

Adipose-Derived Stem Cells Improve Survival of Random Pattern Cutaneous Flaps in Radiation Damaged Skin

Abstract: These findings suggest that ADSCs have a potential for enhancing the blood supply of random pattern skin flaps after radiation injury. This mechanism might be both neovascularization and vasodilation along with endothelial repair. Further studies are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…Since the tissue involving the fistula was expected to be poorly vascularized and fibrotic due to previous operations and radiation injury, we tried to assist the healing process by injecting SVF. Hasdemir et al [11] experimentally showed that adipose-derived stem cells improved skin flap survival and a similar approach was undertaken for this case. Considering that no bulky lipotransfer was carried out in this caseinstead, only a thin mucosal flap was used-we expect that the angiogenic and regenerative effects of SVF could have assisted in the healing of the friable tissue.…”
Section: Discussionmentioning
confidence: 84%
“…Since the tissue involving the fistula was expected to be poorly vascularized and fibrotic due to previous operations and radiation injury, we tried to assist the healing process by injecting SVF. Hasdemir et al [11] experimentally showed that adipose-derived stem cells improved skin flap survival and a similar approach was undertaken for this case. Considering that no bulky lipotransfer was carried out in this caseinstead, only a thin mucosal flap was used-we expect that the angiogenic and regenerative effects of SVF could have assisted in the healing of the friable tissue.…”
Section: Discussionmentioning
confidence: 84%
“…To our knowledge, this is the first evidence showing that ASCs may have an enhancing effect on blood vessel size after burn grafting. Vasodilation has been hypothesized to be a potential mechanism of the increase in blood flow due to ASCs , and clearly may be a factor in the current model. ASCs have also been shown to have other effects on wound healing such as acceleration of reepithelialization both in ocular wounds and in cutaneous wounds in diabetic rats .…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism may be both neovascularisation and vasodilation in addition to endothelial repair. 204 A clinical study of the treatment of radiotherapy-induced injury by lipoaspirate-containing ADSCs showed improved outcomes for 20 grade 3 or 4 patients on the Late Effects Normal Tissue Task force -Subjective, Objective, Management, Analytic (LENT-SOMA) scale measuring severity of radiation effects, with improvement or remission of symptoms in all 20 patients. 205 Further investigation of the effects of adjuvant cancer therapies, both cytotoxic and targeted on ADSC-based tissue regeneration, is required before this method of breast reconstruction can be considered for translation into the clinical setting.…”
Section: Targeted Therapiesmentioning
confidence: 99%